Organizational Justice on Innovative Work Behavior with Knowledge Sharing as a Mediating Variable - Virha Dilla Fahira; Sulastri Sulastri (Human Resource Management Studies, 2022)
The purpose of this study were to analyze the relationship between organizational justice and innovative work behavior when knowledge sharing is a mediating variabel to employee PT. Bank Pembangunan Daerah West Sumatera. The population in this study were all employee in the PT. Bank Pembangunan Daerah West Sumatera as many as 253 employee. The number of samples unsed in the study was 155 employee using the proportional cluster simple random sampling technique. The research design used in this study is causality research. The data analysis technique used is the Structural Equational Model (SEM) with the help of the SmartPLS 3.0 The results of this study revealed that: (1) Organizational justice has a significant effect on innovative work behavior. (2) The influence of organizational justice has a significant effect on knowledge sharing. (3) The influence of knowledge sharing on innovative work behavior. (4) knowledge sharing mediating the organizational justice and innovative work behavior to employee at the PT. Bank Pembangunan Daerah West Sumaterat.